2017
DOI: 10.1371/journal.pone.0176576
|View full text |Cite
|
Sign up to set email alerts
|

Candidemia in the elderly: What does it change?

Abstract: BackgroundCandidemia is a life-threatening fungal infection and it can affect patients of all ages. Characterization of candidemia in the elderly is lacking.MethodsWe performed a retrospective study of adults (≥ 18 years) with candidemia diagnosed in our center in 2010–2015. Demographics, comorbidities, clinical and microbiologic characteristics, antifungal treatment and outcome were compared between older (≤65 years) and younger (>65 years) patients.ResultsAmong 302 patients with candidemia identified during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 27 publications
4
70
0
5
Order By: Relevance
“…Amphotericin B is not metabolised, and thus changes in drug metabolism or pharmacokinetic drug-drug interactions do not play a significant role [49]. The effectiveness of amphotericin B could be reduced in elderly as a recent study found a trend towards higher minimum inhibitory concentration (MIC) values for C. albicans in elderly than in younger patients treated for Candida infections, potentially due to the fact that older patients have been exposed more often to antibiotic and antifungal treatments, resulting in the selection of less susceptible strains [1]. Isolates were, however, still susceptible according to the EUCAST (European Committee on Antimicrobial Susceptibility Testing) clinical breakpoints (http://www.eucas t.org/clini cal_break point s/).…”
Section: Amphotericin Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Amphotericin B is not metabolised, and thus changes in drug metabolism or pharmacokinetic drug-drug interactions do not play a significant role [49]. The effectiveness of amphotericin B could be reduced in elderly as a recent study found a trend towards higher minimum inhibitory concentration (MIC) values for C. albicans in elderly than in younger patients treated for Candida infections, potentially due to the fact that older patients have been exposed more often to antibiotic and antifungal treatments, resulting in the selection of less susceptible strains [1]. Isolates were, however, still susceptible according to the EUCAST (European Committee on Antimicrobial Susceptibility Testing) clinical breakpoints (http://www.eucas t.org/clini cal_break point s/).…”
Section: Amphotericin Bmentioning
confidence: 99%
“…Invasive Candida infections are associated with high morbidity and mortality [2]. The most important Candida species causing invasive disease are C. albicans, C. glabrata, C. krusei, C. parapsilosis and C. tropicalis [1]. Rapid initiation of appropriate antifungal therapy with adequate exposure is needed to achieve optimal treatment outcomes [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Studies with diverse population have shown that elderly patients have higher mortality [130]. In these patients, a combination of comorbidity, poor clinical situation, and more pathogenic species might contribute to their mortality [131]. A pooled analysis from patients included in randomized clinical trials comparing micafungin and amphotericin B showed differences among geographic regions, severity of disease (measured with Apache score for patients critically ill), and catheter removal [132].…”
Section: Discussionmentioning
confidence: 99%
“…We also discuss the complications of postoperative recovery compared to medical treatment alone in this literature review. Candida endocarditis is an emerging disease and a growing health concern globally, especially among the elderly population and immunosuppressed [23]. Additionally, patients needing long-term hospital care with indwelling devices and catheters often suffer from unwanted life-threatening nosocomial infections [10].…”
Section: Introductionmentioning
confidence: 99%